38. ASSESMENT OF THE QUALITY OF HUMAN RESOURCES IN THE HEALTHCARE SECTOR OF BINH DUONG PROVINCE IN 2024 (Vietnam Journal of Community Medicine, 2025)
Objective: Evaluating the Current Quality of Human Resources in the Healthcare Sector of Binh Duong province in 2024.Methods: descriptive cross-sectional study, collecting data from all statistical reports on human resources, organizational structure, plans, and operational directions of the healthcare sector in Binh Duong Province for 2024. In addition, in-depth interviews will be conducted with 11 leaders from the Department of Health, provincial hospitals, and district/city health centers.Results: In 2024, the healthcare sector in Binh Duong Province comprises a total of 11,463 personnel, including 4,665 individuals in regular employment and 6,798 in non-regular positions. The density of healthcare workers is 39.12 per 10,000 population, with the number of physicians at 8.66 per 10,000 population. Within the public healthcare system, personnel with postgraduate qualifications constitute 10.1%, those with undergraduate degrees account for 34.2%, and other qualifications represent 55.7%. During the period from 2020 to 2024, Binh Duong Province successfully recruited 191 physicians. Additionally, it trained 161 postgraduate doctors. The province also produced 323 general practitioners, 20 traditional medicine physicians, 6 preventive medicine doctors, 3 oral and maxillofacial surgeons, 11 laboratory technicians, 11 pharmacists, and 22 midwifery nurses.Conclusion: he healthcare workforce and the number of physicians per 10,000 population in Binh Duong Province are below the national average. The implemented policies aimed at attracting human resources are gradually demonstrating their effectiveness.
Keywords: Human resources; Human resourcesư